Field dimension and skill level constrain team tactical behaviours in small-sided and conditioned games in football - Silva, P.; Duarte, R.; Sampaio, J.; Aguiar, P.; Davids, K.; Araújo, D.; Garganta, J. (Journal of Sports Sciences, 2014)
This study analysed the influence of field dimension and players` skill level on collective tactical behaviours during small-sided and conditioned games (SSCGs). Positioning and displacement data were collected using global positioning systems (15 Hz) during SSCGs (Gk+4 v. 4+Gk) played by two groups of participants (NLP- national-level and RLP-regional-level players) on different field dimensions (small: 36.8 × 23.8 m; intermediate: 47.3 × 30.6 and large: 57.8 × 37.4 m). Team tactical performance was assessed through established dynamic team variables (effective playing space, playing length per width ratio and team separateness) and nonlinear signal processing techniques (sample entropy of distances to nearest opponents and the teams` centroids` mutual information). Results showed that the effective playing space and team separateness increased significantly with pitch size regardless of participant skill level (P < 0.001, ny2 = 0.78 and P < 0.001, ny2 = 0.65, respectively). Playing length per width ratio increased with pitch size for the NLP but was maintained at a relatively constant level by RLP across treatments indicating different playing shapes. There was significantly more irregularity in distances to nearest opponents for the NLP in small (P = 0.003) and intermediate fields (P = 0.01). Findings suggest that tactical behaviours in SSCGs are constrained by field size and skill level, which need to be considered by coaches when designing training practices.